A Note on the Solution of the Von Kármán Equations Using Series and Chebyshev Spectral Methods. (4th October 2010) - Makukula Makukula, Zodwa G. Zodwa G.; Sibanda Sibanda, Precious Precious; Motsa Motsa, Sandile Sydney Sandile Sydney
Abstract : The classical von Kármán equations governing the boundary layer flow induced by a rotating disk are solved using the spectral homotopy analysis method and a novel successive linearisation method. The methods combine nonperturbation techniques with the Chebyshev spectral collocation method, and this study seeks to show the accuracy and reliability of the two methods in finding solutions of nonlinear systems of equations. The rapid convergence of the methods is determined by comparing the current results with numerical results and previous results in the literature.